The effect of Green Marketing, Brand Image, Advertising and Price on Purchasing Decisions - Ramadhan, Muhammad; Simon, Zainal Zawir; Zhafiraah, Nazma Riska (Marketing and Business Strategy, 2024)
This research aims to determine whether or not green marketing, brand image, advertising, and price influence purchasing decisions for AQUALife products. The population of this research is consumers of AQUALife products in the Central Jakarta area. The sample for this research method used a questionnaire via Gform for a month with a total of 120 respondents. The sampling technique uses a non-probability method, with a purposive sampling technique through distributing questionnaires. The data analysis methods used are multiple regression analysis, t-test (partial), and f-test (simultaneous). The research results show that: (1) Green marketing has no significant effect on purchasing decisions. (2) Brand image has a positive and significant effect on purchasing decisions. (3) Advertising has a positive and significant effect on purchasing decisions. (4) Price has a positive and significant effect on purchasing decisions. Managerial implications: Managers need to ensure products and production processes comply with environmentally friendly principles, managers need to ensure consistent brand image across all marketing channels, managers need to develop competitive pricing strategies, managers need to understand competitors' prices and their price position in the market to maintain competitiveness.